Evaluation of malignant breast masses with abbreviated breast magnetic resonance imaging - Yılmaz, Ebru; Güldoğan, Nilgün (The European Research Journal, 2023)
Objectives: Our study aimed to investigate the sensitivity of the abbreviated magnetic resonance imaging (MRI) in the detection of tumors in breast cancer patients. Methods: Patients who underwent breast MRI between March 2018 and October 2021 were reviewed retrospectively. Patients with a histologic diagnosis of breast malignancy were included in the study. Patients who underwent a biopsy or an interventional procedure before the MRI examination and who received neoadjuvant chemotherapy were excluded from the study. Abbreviated MR protocol included a pre-contrast T1-weighted, 1st minute contrast-enhanced T1-weighted, and 1st minute subtracted series. Additionally, 2nd minute post-contrast series were evaluated. Results: A total of 83 lesions with a histologic diagnosis of breast cancer were evaluated in 81 patients. The mean age of the patients included in the study was 51.08 years (range: 27-79 years). Seventy-four of the 83 breast lesions showed contrast enhancement in the 1st minute contrast-enhanced images and subtraction images (sensitivity 89.1%). When missed cases were re-evaluated all of them were visible in the second-minute contrast-enhanced series. Conclusions: In this study, malignant lesions could be detected with high-sensitivity abbreviated MRI protocol and the addition of second-minute contrast-enhanced series to the protocol significantly improve lesion detection. We believe that MRI with the abbreviated MRI protocol can be used for screening purposes in high-risk women with dense breasts.